Current management strategies for osteochondral lesions of the talus. (1st February 2021) - Hurley, Eoghan T.; Stewart, Sarah K.; Kennedy, John G.; Strauss, Eric J.; Calder, James; Ramasamy, Arul
Abstract : The management of symptomatic osteochondral lesions of the talus (OLTs) can be challenging. The number of ways of treating these lesions has increased considerably during the last decade, with published studies often providing conflicting, low-level evidence. This paper aims to present an up-to-date concise overview of the best evidence for the surgical treatment of OLTs. Management options are reviewed based on the size of the lesion and include bone marrow stimulation, bone grafting options, drilling techniques, biological preparations, and resurfacing. Although many of these techniques have shown promising results, there remains little high level evidence, and further large scale prospective studies and systematic reviews will be required to identify the optimal form of treatment for these lesions. Cite this article: Bone Joint J 2021;103-B(2):207–212.